PENGEMBANGAN SISTEM INFORMASI DOKTER KELUARGA (STUDI KASUS PADA SALAH SATU KLINIK DI KELURAHAN BULUSAN) - Widiyantoro, Rio; Dharmawan, Yudhy; Mawarni, Atik; Agusyahbana, Farid (Jurnal Kesehatan Masyarakat (e-Journal), 2016)
A clinic is a health care facility that provides personal heatlh treatment. The clinic used in this research have problems in registration, finance and pharmacy divisions. The registration division has duplicates of patients data and it takes time for officers to find those data. The Finance division periodic reports are too simple and the pharmacy division have to record everything in a book so its hard to oversee how much medicine is left or how much is used in a period of time. These problems are caused by inadequat information system.The purpose of this research is to develop a computer-based information system using rapid action development method.This is a qualitative development research. Information network is developed in accordance to the problems of registration, finance and pharmacy divisions. The subjects of this research are the user of the system which includes a single staff for each divisions. The devepment of the system uses the Rapid Application Development (RAD) method while the evaluation of the results uses End User Computing (EUC). RAD includes user needs assessment, design and implementation. EUC evaluates the conent, accuracy, format, timeliness and user compatibility.The results of this research is a information system that have menu, input form in each section of clinic, database and report on each section. Â shows that the information system is applied in the clinic. After the system was developed, it was evaluated according to each users. While the pharmacy division cannot be evaluated because of retirement, evaluations of the other two divisions sows that this system has provided adequat information prcessing and is ready to be used.